Social Enterprise Location in Economy (Economic and Political Thought, 2011)
The article presents: a concept of a social enterprise from the Europeanand American perspective; interpretational misunderstandings connectedwith equating a social enterprise only with the social aims of its functioning;a lack of social enterprise criteria fulfillment by thousands of non-profitorganizations, foundations and associations in the Polish social and economicreality; the position of a social enterprise in the humanizing theory of business.The article also attempts to position a social enterprise in the theory ofconfirmation and to find there a place for it from the point of view of theEuropean interpretation as well as the American one. It starts a discussionabout the research into social enterprises carried out by the authors.